Potensi Aktivitas Supresi Respon Imun Sinovial sebagai JNK Pathway Inhibitor dalam Tatalaksana Osteoartritis - Renti Kusumaningrum Samosir; Emeraldha Theodorus; Debby Cinthya Damiri Valentina; Theodora Agverianti (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
ABSTRACT Introduction: Osteoarthritis (OA) is a degenerative joint disease affecting 10-15% population of adults above 60 years old. Prevalence rate of the disease in Indonesia in 2013 is 8,1% over the populations. Osteoarthritis is a slow progressive erosion of cartilage components which caused decreased of physical activity level and quality of life. Treatment for osteoarthritis can prevent the progressiveness of the disease. Discussion: Degradation of cartilage joint and subchondral bonein OA patients iscaused by mechanical stress or trauma. Trauma and the overuse of jointscouldrelease oxidative stress and activate sinovial immune response,IL-1 and TNF-? specifically. Activation of immune response can cause the decreased of aggrecans, decreased synthesis of hyaluronic acid which produce lubricant of joints, and impairment of c-Jun NH 2-terminal Kinase (JNK) signalling pathway which cause cartilage degradation and may lead to significant pain. JNKpathway inhibitor potencytoprevent and treat OA can inhibit cartilage degradation. Several compounds which are used to inhibit those proinflammatory cytokines activation are melatonine, vildagliptin (DPP-4 inhibitor), epigallocathecin-3-gallate (EGCG)and Lycorine. Conclusion: Inhibition of JNK pathway which is involved in the regulation of differentiation and apoptosis after oxidative stress exposureare supposed to decrease cartilage degradation significantly, so that it could be developed as a novel therapy modality to prevent worsening the disease of patients with OA. Keywords: Cytokine, JNK pathway inhibitor, Osteoarthritis, Treatment